The Unusual Pattern: Conspicuous Consumption of Housing in Thai Real Estate Market - Lertwanichkijkul, Jiraporn (2006)
A research study on an unusual pattern in conspicuous housing consumption in Thai real estate market by gaining insights through the study of Thai upper class consumers who engage in such consumption in regard to their specific motives. The qualitative research methodology was applied with the use of in-depth and focus group interviews given that the nature of this dissertation study aimed to explore consumer behavior in a social context. The five main research areas of interests and their findings are as follow; Thai consumers are more materialistic and engage in conspicuous consumption in opposition to the former proposition of collectivistic countries are negatively related to materialism and conspicuous consumption (Wong, 1997); Thai culture is tight and high in conformity in divergent to Thailand is a country of prototypical loose culture proposed by Triandis (1989); Thai upper class consumers are in reality sophisticatedly cultivating both cultural dimensions of individualism and collectivism; in deviation to earlier literatures which explain innovators are independent of interpersonal influence pragmatically not applicable in all cultural contexts given that Thai innovators are highly receptive to new products ideas/concepts, yet they are susceptible to interpersonal influence and pay ATSCI as they are collectivistic culturally embedded individuals; and to the last area of research interests - Thai culture is an exceptional case of collectivistic culture that is low in ethnocentrism who preferably consumes the FCCP conspicuous products in differing view to Steenkamp et al (1999) who proposed the collectivistic countries are high in ethnocentrism and the product should be positioned as LCCP.